2022
DOI: 10.3390/v14081831
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Analyses of Grapevine Leafroll-Associated Virus 3 Infection in Leaves and Berries of ‘Cabernet Franc’

Abstract: Grapevine leafroll-associated virus 3 (GLRaV-3) is one of the most important viruses affecting global grape and wine production. GLRaV-3 is the chief agent associated with grapevine leafroll disease (GLRD), the most prevalent and economically destructive grapevine viral disease complex. Response of grapevine to GLRaV-3 infection at the gene expression level is poorly characterized, limiting the understanding of GLRaV-3 pathogenesis and viral-associated symptom development. In this research, we used RNA-Seq to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 83 publications
2
4
0
Order By: Relevance
“…Regardless of the grapevine cultivar, a very diverse virome was detected at both the asymptomatic and symptomatic stages and a large majority (83.33%) of the plants expressed virus-like symptoms in autumn. This is consistent with the findings of several studies 18,19 that observed that virus-like symptoms were more prevalent in grapevine in autumn than in summer.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Regardless of the grapevine cultivar, a very diverse virome was detected at both the asymptomatic and symptomatic stages and a large majority (83.33%) of the plants expressed virus-like symptoms in autumn. This is consistent with the findings of several studies 18,19 that observed that virus-like symptoms were more prevalent in grapevine in autumn than in summer.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in line with previous studies that found that the genes involved in cell-wall softening and expansion in GLRaV3-infected grapevine leaves were downregulated, suggesting that the presence of other symptomatic viruses (e.g. GAMaV and GPGV) was not interfering with GLRaV3 symptomatology 14,19 . In addition, polyketide (e.g.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…GLRaV-3 (genus Ampelovirus) is one of the most widespread and harmful grapevine viruses [45,46]. It is known as the main pathogen of grapevine leafroll disease (GLD) [47].…”
Section: Grapevine Leafroll-associated Virusmentioning
confidence: 99%
“…Moreover, with advances in the field of high throughput sequencing (HTS), research focus has shifted to sequencing-based strategies [ 23 ]. Limited functional studies have been conducted on grapevine virus encoded proteins, and the majority of current research focuses on identifying differentially expressed genes and elucidating the aetiology of grapevine diseases [ 24 , 25 , 26 , 27 , 28 ]. In this study, two complementary techniques were employed to identify interactions between proteins encoded by GLRaV-3 with the aim to gain a better understanding of the role of virus-encoded proteins in virion assembly and movement of members of the genus Ampelovirus .…”
Section: Introductionmentioning
confidence: 99%